Framing research on school principals' identities - Crow, Gary; Day, Christopher; Moller, Jorunn (Taylor & Francis, 2016)
This paper provides a basis for a tentative framework for guiding future research into principals’ identity construction and development. It is situated in the context of persisting emphases placed by government policies on the need for technocratic competencies in principals as a means of demonstrating success defined largely as compliance with demands for the improvement in student test scores. Often this emphasis is at the expense of forwarding a broader view of the need, alongside these, for clear educational values, beliefs and practices that are associated with these. The framework is informed by the theoretical work of Wenger and Bourdieu as well as recent empirical research on the part played by professional identity and emotions in school leadership. In the paper, we highlight different lines of inquiry and the issues they raise for researchers. We argue that the constructions of school leadership identities are located in time, space and place, and emotions reflect complex leadership identities situated within social hierarchies which are part of wider structures and social relations of power and control.